The Impact of Collective Narcissism on National Security: A Psychological Perspective on Nationalism - Haidari, Ikrima Khansa; Eri Radityawara Hidayat; Ichsan Malik (CV. AFDIFAL MAJU BERKAH, 2025)
Collective narcissism can be defined as a group's belief in possessing certain unrecognized privileges. In contrast to patriotism, which reflects genuine affection for one's country, collective narcissism tends to be defensive and compensatory. This study examines the impact of collective narcissism, which serves as the foundation of nationalism, on national security. A literature review methodology was employed to explore the psychology of nationalism and the effects of collective narcissism on national security. The findings revealed that collective narcissism has a detrimental impact on national security, including the erosion of democracy, social polarization, the proliferation of prejudice, and the increased dissemination of conspiracy theories within society. However, the research also suggests that these negative consequences can be mitigated by implementing interventions that enhance positive prosocial emotions and social awareness.